Efficacy and safety of super selective bronchial artery coil embolisation for haemoptysis: a single-centre retrospective observational study - Daijiro Kabata; Ayumi Shintani; Masanori Akira; Masahiko Hara; Hideo Ishikawa; Misaki Ryuge; Jun Takafuji; Mihoko Youmoto; Yukio Nagasaka; Kouji Yamamoto (BMJ Open)
Objectives Evidence on the safety and long-term efficacy of super selective bronchial artery embolisation (ssBAE) using platinum coils in patients with haemoptysis is insufficient. The objective of the present study was to evaluate the safety and the 3-year postprocedure haemoptysis-free survival rate of de novo elective ssBAE using platinum coils rather than particles for the treatment of haemoptysis.Design A single-centre retrospective observational study.Setting Hemoptysis and Pulmonary Circulation Center in Japan.Participants A total of 489 consecutive patients with massive and non-massive haemoptysis who underwent de novo elective ssBAE without malignancy or haemodialysis.Interventions ssBAE using platinum coils. All patients underwent CT angiography before the procedure for identifying haemoptysis-related arteries (HRAs) and for procedural planning.Primary and secondary outcome measures The composite of the 3-year recurrence of haemoptysis and mortality from the day of the last ssBAE session. Each component of the primary end point and procedural success defined as successful embolisation of all target HRAs were also evaluated.Results The median patient age was 69 years, and 46.4% were men. The total number of target vessels was 4 (quartile 2–7), and the procedural success rate was 93.4%. There were 8 (1.6%) major complications: 1 aortic dissection, 2 symptomatic cerebellar infarctions and 5 mediastinal haematoma cases. The haemoptysis-free survival rates were estimated by the Kaplan-Meier analysis at 86.9% (95% CI 83.7% to 90.2%) at 1 year, 79.4% (74.8% to 84.3%) at 2 years and 57.6% (45.1% to 73.4%) at 3 years. Although not statistically significant by the adjusted analysis of variance with multiple imputation of missing variables, cryptogenic haemoptysis tended to show the most favourable outcome and non-tuberculous mycobacterium showed the worst outcome (adjusted p=0.250).Conclusions We demonstrated the safety and long-term efficacy of elective ssBAE using platinum coils and established that it can be a valuable therapeutic option for treating patients with haemoptysis.